2012
DOI: 10.4161/hv.18752
|View full text |Cite
|
Sign up to set email alerts
|

The safety profile ofHaemophilus influenzaetype b–Neisseria meningitidisserogroups C and Y tetanus toxoid conjugate vaccine (HibMenCY)

Abstract: The safety profile of HibMenCY was compared with licensed Hib conjugate vaccines in a pooled analysis that included more than 8,500 subjects who were administered a four-dose series of HibMenCY or commercially available Hib vaccines at 2, 4, 6 and 12–15 mo of age in two primary vaccination and two fourth dose phase 3 studies. In all studies, HibMenCY or Hib vaccine was co-administered with age-appropriate, routinely recommended vaccines. In one primary and one fourth dose study (n = 4180), local and general sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…The safety profile of Hib-MenCY-TT in our study was similar to that observed in previous studies which evaluated its co-administration with the routine recommended vaccines (DTaP-HBV-IPV, 7-valent pneumococcal conjugate vaccine, mumpsmeasles-rubella vaccine, and varicella virus vaccine). 17 The safety profiles of HRV, PCV13 and HAV were also similar when coadministered with Hib-MenCY-TT or Hib-OMP, which is also consistent with the results obtained when other routine childhood vaccines were co-administered with Hib-MenCY-TT. 11 A study limitation was the high drop-out rate observed during the study period as nearly one fourth of participants did not complete the study and nearly half of participants were excluded from the primary ATP immunogenicity cohort, because we had not planned to bleed most of these participants.…”
Section: Discussionsupporting
confidence: 84%
“…The safety profile of Hib-MenCY-TT in our study was similar to that observed in previous studies which evaluated its co-administration with the routine recommended vaccines (DTaP-HBV-IPV, 7-valent pneumococcal conjugate vaccine, mumpsmeasles-rubella vaccine, and varicella virus vaccine). 17 The safety profiles of HRV, PCV13 and HAV were also similar when coadministered with Hib-MenCY-TT or Hib-OMP, which is also consistent with the results obtained when other routine childhood vaccines were co-administered with Hib-MenCY-TT. 11 A study limitation was the high drop-out rate observed during the study period as nearly one fourth of participants did not complete the study and nearly half of participants were excluded from the primary ATP immunogenicity cohort, because we had not planned to bleed most of these participants.…”
Section: Discussionsupporting
confidence: 84%
“…21,29 Solicited local (injection site pain, redness, and swelling) and general (fever ≥38°C, drowsiness, irritability, and loss of appetite) symptoms occurred at similar rates in both groups, with the exceptions of pain at the injection site and irritability, which were reported at significantly (P < .05) lower rates after vaccination with Hib-MenCY-TT than Hib. 28 Similar rates were observed for SAEs, new onset of chronic disease, rash, and adverse events prompting emergency room visits after vaccination with either Hib-MenCY-TT or Hib vaccines. Only anemia was reported more frequently in the Hib group than the Hib-MenCY-TT group (0.1% vs 0.0%, respectively; P = .03).…”
Section: Adverse Eventssupporting
confidence: 55%
“…21 Safety was also evaluated in a pooled analysis of more than 8500 infants who received a 4-dose series of either Hib-MenCY-TT (n = 6414) or Hib vaccines (n = 2157), in addition to routine age-appropriate vaccines. 28 The analysis combined 2 primary vaccination and 2 dose 4 studies. 21,29 Solicited local (injection site pain, redness, and swelling) and general (fever ≥38°C, drowsiness, irritability, and loss of appetite) symptoms occurred at similar rates in both groups, with the exceptions of pain at the injection site and irritability, which were reported at significantly (P < .05) lower rates after vaccination with Hib-MenCY-TT than Hib.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…Despite the addition of MenC and Y antigens, the reactogenicity of HibMenCY-TT does not differ from that associated with administration of Hib-TT vaccine [ 33 , 36 , 37 ]. A pooled safety analysis that included more than 8,500 participants from two primary vaccination and two-fourth dose phase III clinical trials found the incidence of serious adverse events, adverse events and solicited local and general systemic symptoms were similar following HibMenCY-TT and licensed Hib vaccines [ 39 ]. Rates of pain at the injection site and irritability were significantly lower following HibMenCY-TT than commercially available Hib vaccines [ 39 ].…”
Section: Clinical Trial Datamentioning
confidence: 99%